2016
DOI: 10.4049/jimmunol.1501351
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic CD38 Monoclonal Antibody Daratumumab Induces Programmed Cell Death via Fcγ Receptor–Mediated Cross-Linking

Abstract: Emerging evidence suggests that FcγR-mediated cross-linking of tumor-bound mAbs may induce signaling in tumor cells that contributes to their therapeutic activity. In this study, we show that daratumumab (DARA), a therapeutic human CD38 mAb with a broad-spectrum killing activity, is able to induce programmed cell death (PCD) of CD38+ multiple myeloma tumor cell lines when cross-linked in vitro by secondary Abs or via an FcγR. By comparing DARA efficacy in a syngeneic in vivo tumor model using FcRγ-chain knocko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
189
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(195 citation statements)
references
References 47 publications
1
189
0
5
Order By: Relevance
“…To assess rare populations and their CD38 + subsets, WB samples from the SIRIUS trial were manually gated and analyzed. Beyond confirmation of the previously reported daratumumab‐mediated depletion of immune‐suppressive populations, like CD38 + T regs (CD4 + CD25 + CD127 − ) (Fig. A), our high‐dimensional cytometry analysis enabled the first evaluation of basophils (CD45 − CD123 + HLA‐DR − ) under daratumumab treatment.…”
Section: Resultssupporting
confidence: 80%
“…To assess rare populations and their CD38 + subsets, WB samples from the SIRIUS trial were manually gated and analyzed. Beyond confirmation of the previously reported daratumumab‐mediated depletion of immune‐suppressive populations, like CD38 + T regs (CD4 + CD25 + CD127 − ) (Fig. A), our high‐dimensional cytometry analysis enabled the first evaluation of basophils (CD45 − CD123 + HLA‐DR − ) under daratumumab treatment.…”
Section: Resultssupporting
confidence: 80%
“…Other effector cells, such as granulocytes, which are not depleted by daratumumab, are also capable of mediating ADCC and may contribute to the efficacy of daratumumab. Moreover, in addition to ADCC, daratumumab has several known mechanisms of action that may also contribute to its efficacy, including CDC, 8 antibody-dependent cellular phagocytosis, 9 apoptosis, 13 and modulation of CD38 enzymatic activity.…”
Section: Discussionmentioning
confidence: 99%
“…DARA induces killing of tumor cells, mainly via complement-dependent cytotoxicity (CDC), antibody-dependent cellular cytotoxicity (ADCC) (20) and antibody-dependent cellular phagocytosis (ADCP) by macrophages (mϕ) (21) in MM and Burkitt lymphoma (BL) cell lines. In addition, DARA induces apoptosis upon secondary cross-linking (22). Recent studies have revealed previously unknown immunomodulatory effects of DARA where CD38-expressing immunosuppressive regulatory T and B cells, and myeloid-derived suppressor cells are highly sensitive to DARA treatment (23).…”
Section: Introductionmentioning
confidence: 99%